INCREASING EFFECT OF EMPLOYEE WORK ETHICS AND TRAINING ON EMPLOYEE PERFORMANCE AND SERVICE QUALITY AT PT XL AXIATA RIAU - Setiawan, Yayat; Junaedi, Achmad Tavip; Chandra, Teddy (Journal of Applied Business and Technology, 2021)
The quality of customer service in companies is often affected by ethics and poor employee performance, lack of employee training on the necessary skills. These challenges lead to companies losing customers, declining quality, and being criticized in terms of service, lack of morale which leads to low productivity and hinders the achievement of PT XL AXIATA's goals. This study aims to determine the effect of employee work ethics and employee training on customer service quality in the service department. In particular, with the main objective to determine the relationship between Employee Performance and Customer Service Quality at PT XL AXIATA, the mediation results of employee training and the influence on the relationship between Employee Performance and Customer Service Quality at PT XL AXIATA. As well as the combined effect of ethics and employee training on the quality of customer service at PT XL AXIATA. The author adopted a descriptive research design. This study uses quantitative methods. The type of data used in this study is primary data, which means that the data is obtained directly by the respondent. In this study, the distribution of questionnaires as many as 83 respondents. The test used to test is a research instrument in the form of validity test, reliability test and classical assumption test. From the results of data processing using the T test (partial) variable Ethics (X1), Employee Training (X2) Able to Influence Employee Performance (Y1) and Service Quality (Y2).